Аспекты энергосбережения в корреляционном развитии традиционных и современных городских пространств в Дубае - Яшар Хусейнзаде Нагаде (ՀՀ ԳԱԱ հրատ.)
Հոդվածն արդիական է այն երկրների համար, որոնք ունեն շոգ կլիմայական պայմաններ: Առաջարկվում են ցանկացած որոշակի ժամանակահատվածում անձրեւներ առաջացնելու ուղիներ՝ դրանով իսկ մարդկանց համար ստեղծելով բարենպաստ միկրոկլիմայական պայմաններ, ջրով սնուցելով գյուղատնտեսական նշանակության հողերը։ This article is urgent for countries having hot climatic conditions. Ways of artificial precipitation or rainmaking at any specific time are proposed, thereby creating beneficial microclimatic conditions for people, supplying agricultural soil with water for irrigation purposes and finally providing the recreational and green areas with greenery without expectations for natural rain water. In this way the urgent problems of hot countries are solved.
Keywords: Electrical engineering; Electronics; Nuclear engineering; Fine Arts; Architecture